2016
DOI: 10.1016/j.jare.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Repair bond strength of dual-cured resin composite core buildup materials

Abstract: The reparability of dual-cured resin composite core buildup materials using a light-cured one following one week or three months storage, prior to repair was evaluated. Two different dual-cured resin composites; Cosmecore™ DC automix and Clearfil™ DC automix core buildup materials and a light-cured nanofilled resin composite; Filtek™ Z350 XT were used. Substrate specimens were prepared (n = 12/each substrate material) and stored in artificial saliva at 37 °C either for one week or three months. Afterward, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…This was in agreement with Deeb et al (23) and El Askary et al (24) who found that immediately repaired composite has bond strength greater than the delayed one.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with Deeb et al (23) and El Askary et al (24) who found that immediately repaired composite has bond strength greater than the delayed one.…”
Section: Discussionsupporting
confidence: 92%
“…Intergroup comparison showed that groups restored with sonic fill composite (Group A) had significantly lower cuspal deflection as compared to groups restored with Filtek Z350 XT composite (Group B). According to the literature, increased filler content (83.5 wt%)[ 7 ] and decreased percentage volumetric shrinkage of Sonic fill composite (1.6%)[ 8 ] might have resulted in lower cuspal deflection as compared to Filtek Z350 XT composite which have filler content of 78.5 wt%[ 9 ] and percentage volumetric shrinkage of 1.97%. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…31 O critério fratura (do dente e/ou da restauração) também foi citado como prevalente em 33,3% dos artigos avaliados. 6,19,22,24,[32][33][34] De acordo com Demarco et al, 19 o motivo de a fratura ser apresentada como uma das principais razões para falha de restaurações em resina composta pode ser justificado pelo fato de que o material utilizado apresenta um maior módulo de elasticidade e dureza em relação ao dente. Além disso, há a influência do tamanho cavitário (desgaste dental) nessas falhas, sendo que dentes com preparos cavitários maiores apresentam maiores chances de desenvolver fratura ao longo do tempo.…”
Section: Discussionunclassified